FAKTOR RISIKO KEJADIAN TB PARU PADA ANAK USIA 1â5 TAHUN DI KABUPATEN KEBUMEN - , RD. Halim; , dr.Roni Naning, M.Kes, Sp.Ak, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Tuberculosis (TB) is a major public health problem. It is estimated that the total number of patient of TB in Indonesia about 10% of TB worldâs patients, Indonesia is in the third place. It is estimated that patient of TB children 5%-6% per year. In 1989, WHO estimated that new cases of TB children are 1.3 million every year. It is estimated that cases of TB children less than 15 years old is 15%. While the data of TB children casefinding in 2007 up to the third quarter of 2010 was 432 cases. Objective: To determine risk factors for incidence of tuberculosis in children. Method: This was an observational study with case control design. Subjects were children aged 1-5 years old who were diagnosed TB. The independent variables were education level, economy status, immunization BCG, humidity, illumination, ventilation, type of floor, cooking fuel, density of occupancy, contact history and PM 10. The total number of samples were 216 persons. cases were 72 and controls were 144. Cases were patients of TB children which were recorded in TB register at District Health Office of Kebumen. Controls were taken from the places where cases got treatment and the neighbors. Data were collected by interviewing and observation. Data analysis by using conditional logistic regression Results:Risk factors for incidence of TB in children were history of contact with TB patients OR 8.72 (CI=2.449-31.074), humidity of room OR 3.11 (CI=1.166-8.303), cooking fuel OR2.85 (CI=1.148-7.065) and home illumination OR 2.81 (CI=1.031-7.686) were statistically significant. Conclusion: contact history, home humidity, cooking fuel and ineligible home illumination were the most risk factors of the incidence of TB children in Kebumen District.